Intracardiac vs transesophageal echocardiography for percutaneous left atrial appendage occlusion: A meta‐analysis - Velagapudi, Poonam; Turagam, Mohit K.; Kolte, Dhaval; Khera, Sahil; Gupta, Tanush; Garg, Jalaj; Abbott, J. Dawn; George, Isaac; Khalique, Omar; Vahl, Torsten; Nazif, Tamim; Lakkireddy, Dhanunjaya; et al. (Journal of cardiovascular electrophysiology, 2019)
Introduction Percutaneous left atrial appendage closure (LAAC) is typically performed utilizing transesophageal echocardiography (TEE) and fluoroscopy. Intracardiac echocardiography (ICE) can be a suitable alternative to guide implantation. Given the limited data, we performed a meta‐analysis of all studies that compared ICE vs TEE for percutaneous LAAC. Methods A comprehensive literature search was performed in PubMed, Embase, Scopus, Google Scholar, and major scientific conference sessions for published s and manuscripts until 1 August 2018. Studies reporting clinical outcomes comparing TEE vs ICE for endocardial LAAC in human subjects aged greater than or equal to 18 years were included. Two investigators independently extracted the data and individual quality assessment was performed. The analysis was performed using Cochrane Collaboration software, RevMan 5.3. Results Five eligible studies consisting of 1157 patients (ICE‐391 patients and TEE‐766 patients) were included. Four studies were retrospective and one was prospective, nonrandomized. Two studies included Watchman, two included the Amplatzer Cardiac Plug/Amulet device, and one included both devices. There was no significant difference in CHA2DS2VASC or HAS‐BLED scores between both groups. There was no significant difference in acute procedural success between ICE vs TEE (risk ratio, 1.01; 95% CI, 0.99‐1.04; P = 0.24). There was no significant difference in fluoroscopy time (mean difference [MD], 1.84 minutes; 95% CI, 0.59‐4.27; P = 0.14) and total procedure time (MD, −5.06 minutes; 95% CI, −24.6‐14.4; P = 0.61) between both groups. There was also no significant difference in complications including pericardial tamponade, device embolization, and stroke between both groups. Conclusion In our meta‐analysis, ICE was as effective as TEE during percutaneous LAAC.